2015
DOI: 10.1134/s0006297915030062
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms of peptidergic regulation of gene expression during aging of human cells

Abstract: Expression levels of genes encoding specific transcription factors and other functionally important proteins vary upon aging of pancreatic and bronchial epithelium cell cultures. The peptides KEDW and AEDL tissue-specifically affect gene expression in pancreatic and bronchial cell cultures, respectively. It is established in this work that the DNA methylation patterns of the PDX1, PAX6, NGN3, NKX2-1, and SCGB1A1 gene promoter regions change upon aging in pancreatic and bronchial cell cultures in correlation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These compounds exert a variety of functions in the human body and are able to modulate epigenetic mechanisms. There are different reports discussing gene regulatory effects of peptides [5558]. Depending on the peptide, these effects are direct or indirect by binding to receptors and activation of intracellular signaling cascades (Table 1).…”
Section: The Influence Of Peptides On Epigenetic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds exert a variety of functions in the human body and are able to modulate epigenetic mechanisms. There are different reports discussing gene regulatory effects of peptides [5558]. Depending on the peptide, these effects are direct or indirect by binding to receptors and activation of intracellular signaling cascades (Table 1).…”
Section: The Influence Of Peptides On Epigenetic Mechanismsmentioning
confidence: 99%
“…These short “cryptic” peptides can be formed endogenously by proteolytic cleavage of nuclear proteins or by synthesis after which they penetrate the cytoplasmic and nuclear membrane [60, 61]. These peptides are involved in the epigenetic regulation of aging and can have health-promoting effects by for example suppressing age-related increased expression of matrix metalloproteases and caspase-dependent apoptosis [55, 93].…”
Section: The Influence Of Peptides On Epigenetic Mechanismsmentioning
confidence: 99%
“…Previous studies have suggested an epigenetic mechanism of action of ultrashort peptides [17][18][19][20]. In this regard, the aim of the review is to analyze the possible epigenetic mechanisms of the neuroprotective action of short peptides in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Their main function is a normalizing effect on specific organs, replacing or supporting the activity of substances secreted by these morphological structures. They also increase the lifespan of mesenchymal stem cell (MCS) and induce molecular mechanisms that contrast senescence [ 25 ]. They modulate neuronal activity and hinder cognitive degeneration, probably by improving the integration of cellular functions, and thus counteracting the accumulation of free radicals.…”
Section: Introductionmentioning
confidence: 99%